Examining the Relationship Between Foot Length and Ankle Muscle Strength in Swimmers - Tuğba Kocahan; Bihter Akınoğlu; Osman Alper Şener; Adnan Hasanoğlu (Türk Spor ve Egzersiz Dergisi, 2021)
The aim of this study is to examine the relationship between foot length and isokinetic muscle strength of the ankle plantar and dorsiflexor muscles in swimmers. A total of 53 competitive swimmers, 18 women and 35 men, were included in the study. The athletes’ foot length was assessed by calipers, and their ankle plantar and dorsiflexor muscle strength was evaluated with an isokinetic dynamometer. Spearman correlation analysis was used to examine the relationship between athletes' foot length and ankle isokinetic muscle strength. There was a moderate relationship between the foot length of the athletes and the isokinetic muscle strength of the ankle plantar and dorsiflexor muscles at an angular velocity of 60 ° / sec (r = 450/347; p lt;0.05); there was a moderate correlation between the isokinetic strength of the ankle plantar flexor muscles at 180 ° / sec angular velocity (r = 403; p lt;0.05); It was determined that there was no relationship between the isokinetic muscle strength of the ankle dorsi flexor muscles at an angular velocity of 180 ° / sec (r: 0.145; p gt; 0.05). As a result of our study, it was determined that the strength of the ankle plantar and dorsi flexor muscles increased as the foot length increased in swimmers. Based on this result, the idea that foot length can affect ankle muscle strength in swimmers has emerged. However, some studies are needed to examine the effect of this relationship on swimming performance.